Can the Production Smoothing Model of Inventory Behavior be Saved? - Blinder, Alan S. (Quarterly Journal of Economics, 1986)
The production smoothing model of inventory behavior has a long and venerable history and theoretical foundations that seem very strong. Yet certain overwhelming facts seem not only to defy explanation within the production smoothing framework, but actually to argue that the basic idea of production smoothing is all wrong. Most prominent among these is the fact that the variance of detrended production exceeds the variance of detrended sales. This paper first documents the stylized facts. Then it derives the production smoothing model rigorously and explains how the model can be amended to make it consistent with the facts. Finally, it reviews the theoretical and empirical evidence and tries to draw some tentative conclusions.